The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acssynbio.0c00222
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Mediated Control of Polyadenylation for Gene Expression Regulation in Mammalian Cells

Abstract: Small aptamer-based regulatory devices can be designed to control a range of RNA-dependent cellular processes and emerged as promising tools for fine-tuning gene expression in synthetic biology. Here, we design a conceptually new riboswitch device that allows for the conditional regulation of polyadenylation. By making use of ligand-induced sequence occlusion, the system efficiently controls the accessibility of the eukaryotic polyadenylation signal. Undesirable 3′-extended read-through products are counteract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Several groups have developed riboswitches which regulate eukaryote-specific steps in mRNA processing (Figure 1). A notable example is provided in a recent publication by Spöring et al, who reported 5.2-fold suppression of reporter gene expression in human cells mediated by ligand-induced sequestration of the eukaryotic polyadenylation signal (Figure 1a) [66]. This switch was combined synergistically with other regulators such as miRNAs or aptazyme riboswitches to achieve higher regulatory ranges.…”
Section: Riboswitches Regulating Mrna Processingmentioning
confidence: 94%
See 1 more Smart Citation
“…Several groups have developed riboswitches which regulate eukaryote-specific steps in mRNA processing (Figure 1). A notable example is provided in a recent publication by Spöring et al, who reported 5.2-fold suppression of reporter gene expression in human cells mediated by ligand-induced sequestration of the eukaryotic polyadenylation signal (Figure 1a) [66]. This switch was combined synergistically with other regulators such as miRNAs or aptazyme riboswitches to achieve higher regulatory ranges.…”
Section: Riboswitches Regulating Mrna Processingmentioning
confidence: 94%
“…(a) Regulation of polyadenylation.In the absence of ligand, the polyadenylation site (PAS, orange) is bound by the polyadenylation complex (orange), which removes a downstream miRNA target site (miR-T, red) and adds a poly-A tail to enable expression. Ligand binding (purple) to an aptamer domain (blue) sequesters the PAS, blocking processing and promoting mRNA degradation by exonucleases and miRNA-induced silencing[66]. (b) Regulation of splicing by ligand-induced exon skipping.…”
mentioning
confidence: 99%
“…Artificial riboswitch (aptazyme) has been used to regulate gene expression precisely via binding between RNA and ligand (Pu et al, 2020). Aptazyme was utilized to control mRNA cleavage through self-cleavage within the mRNA (Takahashi and Yokobayashi, 2019;Spöring et al, 2020). Aptazyme can be inserted into 5' or 3' UTR of gene mRNA for controlling gene expression (Chen et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%
“…The hammerhead ribozyme (HHR) is the common ribozyme platform (Zhong et al, 2016). When aptamer combines with ligand, the induced conformational change will be transferred to HHR via the communication module, generating cleavage activity (Spöring et al, 2020). OFF-switch and ON-switch are two types of aptazymes (Nomura et al, 2013;Beilstein et al, 2015;Yokobayashi, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Small aptamer-based regulatory devices can be designed to control a range of RNA-dependent cellular processes and emerged as promising tools for fine-tuning gene expression in synthetic biology. Research achieved a polyadenylation-modulating riboswitch with a modest dynamic range which can be functional with different poly(A) signals and proved the modularity of the switch by exchanging the sensor module to a tetracycline aptamer [ 26 ].…”
Section: Introductionmentioning
confidence: 99%